Enhancing Stability of Perovskite Solar Cells to Moisture by the Facile Hydrophobic Passivation - Hwang, Insung; Jeong, Inyoung; Lee, Jinwoo; Ko, Min Jae; Yong, Kijung (American Chemical Society, 2015)
In this study, a novel and facile passivation process for a perovskite solar cell is reported. Poor stability in ambient atmosphere, which is the most critical demerit of a perovskite solar cell, is overcome by a simple passivation process using a hydrophobic polymer layer. Teflon, the hydrophobic polymer, is deposited on the top of a perovskite solar cell by a spin-coating method. With the hydrophobic passivation, the perovskite solar cell shows negligible degradation after a 30 day storage in ambient atmosphere. Suppressed degradation of the perovskite film is proved in various ways: X-ray diffraction, light absorption spectrum, and quartz crystal microbalance. This simple but effective passivation process suggests new kind of approach to enhance stability of perovskite solar cells to moisture.
Keywords: HIGH-PERFORMANCE; EFFICIENT; HYSTERESIS; NANOROD; LIGHT; LAYER